Combining a Phenanthroline Moiety with Peralkylated Guanidine Residues: Homometallic CuII, NiII and ZnII Halide Complexes with Site‐Differentiating Janus Head Ligands. Issue 48 (11th December 2018) - Ortmeyer, Jochen; Vukadinovic, Yannik; Neuba, Adam; Flörke, Ulrich; Henkel, Gerald
Abstract : The unique core portion of Janus head pro‐ligands based on a tailored phenanthroline‐bis(guanidine) architecture has been utilized to generate a multiplicity of homometallic copper(II), nickel(II) and zinc(II) complexes terminated by halide constituents. The bis‐bidentate nitrogen donor ligands provide coordination sites with metal‐differentiating properties which can be loaded successively starting with the phenanthroline interface as can be demonstrated by mononuclear species which form under metal deficient conditions. Furthermore, depending on both the alkylation and metalation stage of the guanidine residues comprising variants with tetramethyl‐, tetraethyl‐, dimethylethylene‐, and dipentylene‐guanidino functionalities, a unique diversity of bi‐ and tetranuclear complexes with multifarious coordination geometries is accessible. The resulting complexes were characterized by low‐temperature X‐ray crystallography, and their redox behavior and magnetochemical properties in solution were analyzed via cyclic voltammetric and NMR techniques (Evans method). In this way, a remarkable equilibrium between the neutral phenanthroline‐bis(guanidine) copper(II) complex (X2 Cu II ‐phenGua‐Cu II X2 ) and the radical monocationic phenanthroline‐bis(guanidine) copper(I)/copper(II) [X2 Cu II ‐phenGua +· ‐(Cu I X2 ) – ] species was identified which affects the chemical characteristics of the presented compounds in solution. Abstract : Based on the unique phenanthroline‐bis(guanidine) architecture of Janus head pro‐ligands, a variety of homometallic Cu II, Ni II and Zn II complexes assembled in multifarious coordination geometries and completed by terminal or bridging halide constituents have been synthesized. Structural configurations, redox behavior and magnetochemical properties of the mono‐, bi‐ and tetranuclear species were characterized via X‐ray crystallographic, electrochemical and NMR techniques.